An Analysis of a Rubber Ball Hand Exercise on Stroke Patient: Case Study - Puspita, Tantri; Heryanti Nur’aeni, Silva (Sean Institute, 2022)
Stroke is a clinical syndrome that initially arises suddenly, progressively rapidly, in the form of a global focal and neurological deficit that lasts 24 hours or more and or can directly cause death, and is solely caused by circulatory disorders to the non-traumatic brain. The main problem that arises in stroke sufferers is the destruction or death of tissue. One of the efforts to recover and assist the patient in movement is the need for action in nursing, namely exercises by grasping a rubber ball. The purpose of this nursing care plan is to analyze the management case in providing nursing care intervention for Mr.A with stroke with the application of a rubber ball hand-held intervention to increase muscle strength and weakness in the Wilayah Kerja Puskesmas Tarogong. The intervention of Nursing Care in stroke patients with the administration of rubber ball hand-held exercises. After being given nursing care with the intervention of providing rubber ball hand-holding exercises for 3 days, the patient muscle strength was raised. The initial muscle strength before the administration of the intervention was 3, and after being given the exercise of grasping the rubber ball was 4. Nursing care in stroke patients with the provision of rubber ball hand-held exercises can increase muscle strength in patients.